Productivity in Chilli (cv. LCA 334) as Influenced by Organic and Inorganic Nutrient Management in Vertisols - S Bharathi; S Surya Kumari; K Uma Jyothi (Journal of Horticultural Sciences, 2011)
A field experiment was conducted at Regional Agricultural Research Station, Lam, Guntur during the kharif season of 2003-04 and 2004-05 in vertisols with an objective to assess effectiveness of organic nutrient package for yield sustainability and to assess inorganic nutrient management package vis-a-vis organic package for yield and quality in chilli cv. LCA 334. Farmers of this region generally use very high doses of inorganic fertilizers with improper nutrient balance which has led to deterioration of productivity and quality of both the produce soil. The experiment was carried out in randomized block design with ten treatments, in combinations of organic and inorganic sources. The organic sources used were: green manure (incorporation of pillipesara), neem cake, Azospirillum, phosphate solubilizing bacteria, VAM and burnt ash, and integrated with 50%, 75% and 100% recommended nitrogen in the form of chemical fertilizer. Results revealed that maximum dry chilli yield ( 5397kg ha-1) was recorded in combined application of green manure, neem cake, Azospirillum, phosphate solubilizing bacteria, burnt ash along with 100% recommended nitrogen.